Predisposing Factors of Vaginal Discharge in Pregnant Women in the Coastal Area of Bengkulu City - Agni, Sinta Oktalia; Dewiani, Kurnia; Versita, Riana; Novianti; Yulyani, Linda (The Indonesian Institute of Science and Technology Research, 2024)
Pregnancy, a natural process, entails physiological discomfort, such as vaginal discharge. This discharge is categorized as normal (physiological) or abnormal (pathological). Normal discharge is colorless, odorless, and not excessive, while abnormal discharge is cloudy, thick, and may have unpleasant odors and itchiness. This study in the coastal area of Bengkulu City aims to identify characteristics of pregnant women and explore predisposing factors for vaginal discharge. Utilizing a quantitative survey method with 107 purposively sampled pregnant women, the study focused on independent variables like Knowledge and Personal Hygiene, with vaginal discharge as the dependent variable. The results indicate that over half of the respondents (57%) demonstrated good knowledge, 52.3% exhibited good personal hygiene behavior, and 61% experienced physiological vaginal discharge. In conclusion, knowledge and personal hygiene emerge as critical factors influencing vaginal discharge in pregnant women.